Raw data from Pure-rotational and Vibro-rotational Raman Lidar signals from MDPI-Sensors 1074075 and retrieved aerosol optical and extiction coefficients - José Alex Zenteno-Hernández; Adolfo Comerón; Alejandro Rodríguez-Gómez; Constantino Muñoz-Porcar; Giuseppe D extquotesingleAmico; Michaël Sicard (PANGAEA, 2021)
The data correspond to measurements along a vertical line of sight carried out by the multiwavelength Raman / elastic EARLINET/ACTRIS lidar at Universitat Politècnica de Catalunya (UPC, Barcelona, Spain) on March, 11th 2020 and on March 21th 2020. sensors-20210202T183221Z-001_Input_files are the raw data files in netCDF format generated by the multiwavelength Raman / elastic EARLINET/ACTRIS lidar at Universitat Politècnica de Catalunya (UPC, Barcelona, Spain) submitted as input to the EARLINET Single Calculus Chain (SCC, https://scc.imaa.cnr.it/) centralized software processing the data and retrieving, among other products, range-resolved aerosol extinction and backscatter coefficients. sensors-1074075_Output_ files contain the netCDF files containing the aerosol extinction and backscatter coefficients retrieved by the SCC.